Diagnostic Accuracy of Multiparametric MRI versus TRUS Biopsy in Clinically Significant Prostate Cancer: Correlation with PSA Derivatives, Urinary PCA3, and Renal Function - Khawar Ali, Abid Abbas, Shaheen Khan Bahadar, Muhammad Iqbal, Abdur Rasheed, Muhammad Omer, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Multiparametric magnetic resonance imaging (mpMRI), transrectal ultrasound (TRUS) biopsy,PSA derivatives, urinary PCA3, and renal function were prospectively evaluated to determine theircollective diagnostic performance in detecting